AN AUTOETHNOGRAPHIC ACCOUNT OF TWO INDONESIAN ACADEMIC RETURNEES EXPERIENCED OF REVERSE CULTURE SHOCK - Irfan Rifai; Mukrim Tamrin (Lembaga Penelitian Universitas Pasundan, 2020)
In this article, we use an autoethnography approach to reflect on our emotional experiences of re-integrating in academic community in two different universities. We start to explore our experience of implementing new knowledge in teaching and researching, demonstrating how we as junior lecturers often making confrontations with the ‘conventional’ and ‘traditional’ sounded educational system which have been practiced by senior colleagues. In this sense, there has been a conflictual emotion which we should address, utilizing our new knowledge or returning back to the existing norms. Whilst exploring our experiences of dealing with conflictual emotional beliefs, we also examine issue such as identity construction as being an academic returnee responding to the confrontation in academic environment. This study results may resonate the concrete condition of academic returnees re-integrating to their academic milieu in other part of the countries.